IMPACT OF ORGANIZATIONAL JUSTICE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR: A STUDY OF EDUCATION SECTOR IN ODISHA - Laxmipriya Das, Suchitra Panigrahi, Dr. Sasmita Mohanty (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this research is to examine the connection between Organizational Justice and Organizational Citizenship Behavior among faculty members of private universities of Bhubaneswar, Odisha. No successful research is performed on the relationship of organizational justice and organizational citizenship behavior in the education field. This research also examined the influence of Organizational Justice on Organizational Citizenship Behavior. Two hundred faculty members of several private universities were participated in this study. The study employed questionnaire for data collection. It was observed that between the two variables there is an essential relationship.